(3OhQ GdUMGaI GdSGNQI ai GdMQcI GdhWfjI GdeUQjI (B1878- 1910(3e(B: s (3OQGSI JWHjbjI Ydi UMa jYbhH UfhY (B/ s - (3QjgGe YHOg EHQGgjes; (3TQja OQhjT GddHGf (B: s; (3YhGWa YHOGdQMef (B: s ((3GdbGgQI (B: s (3QjgGe YHOg EHQGgje (B: s, 2020)
(3GSJgOaJ GdOQGSI QUO h JMdjd h JaSjQ GdOhQ GdPi dYHJg UMa jYbhH UfhY GdSGNQI JLGg GdMQcI GdhWfjI GdeUQjI NdGd eQGMdgG GdeNJdaI GdJi YGUQJgG h bO JMOOJ YjfI GdUMa ai(B: (3GdeSM GdTGed dLejY GdehGO GdSGNQI GdfUjI GdefThQI ai UMa jYbhH UfhY GdSGNQI WhGd aJQI UOhQgG (B(21/3/1295(3g`(B) (3GdehGab (B25 (3eGQS YGe (B1878(3e(B: (3h MJi OjSeHQ YGe (B1910(3e(B: (3h GdJi JfGhdJ Cge bVGjG GdMQcI GdhWfjI GdeUQjI(B: (3GdMGdI GdeUQjI GdGbJUGOjI h GdGLJeGYjI h GdSjGSjI(B: ((3GdOjf GdeUQi(B: (3bQGQGJ GdfXGQI GdeUQjI h COGFgG(B: (3GdJONd GdCLfHi(B: (3MGOKI OfThGi(B): (3GdMQGc GdacQi h GdGLJeGYi hGdSjGSj h jVe(B: ((3GdLeYjGJ GdCgdjI h GdeGShfjI(B: (3GdUMGaI(B: (3eLdS GdfhGH(B: (3GdCMRGH GdSjGSjI(B): (3h GdKhQI GdYQGHjI(B: (3h GdKhQI GdegOjI(B: (3h Ydjg jchf eLed CYOGO UMa GdOQGSI (B411 (3YOO GMJhi Ydi (B1644 (3eGOI SGNQI(B: (3h GYJeOJ GdOQGSI Ydi GdefgL GdJGQjNi(B: (3h CSdhH GdebGQfI GdefgLjI(B: (3ai EWGQ fehPL GdJMdjd Gdehbaj h ESJQGJjLjI Gdehba EVGaI Edi GdfehPL GdPi GbJQMJg GdHGMKI h GdPi jaSQ GdBdjI GdJi GYJeOJ YdjgG GdUMa eMd GdOQGSI ai JhXja GdSNQjI dJCdjH GdQCi GdYGe h GdOaY HGdMQGc GdhWfj(B. (3KeI hLhO GNJdGaGJ ai NWGHGJ UMa GdOQGSI QUOJg GdHGMKI habG(B: (3deJZjQGJ EbJUGOjI JJeKd ai eUGOQ Jehjd GdUMa (B((3GdCejQ eMeO YHOGdMdje (B- (3GdSdWGf YHOGdMejO GdKGfi (B- (3GdLeYjGJ GdeGShfjI(B): (3h eMOOGJ CjOjhdhLjI JJeKd ai GfJeGAGJ eOjQ JMQjQ GdUMa h UGMHgG GdacQjI GdYbGFOjI (B((3GdeGShfjI(B): (3h ejhdg GdSjGSjI GdOGYeI ddLGfH GdaQfSi Ydi MSGH GdEfLdjR(B: (3h eJZjQGJ JJYdb HGfJbGd ebQ EUOGQ GdUMa ef GdbGgQI Edi HGQjSs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdEYdGe (B- (3bSe GdUMGaIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdMQcI GdhWfjI GdeUQjIs; (3GdUMGaI GdSGNQIs; (3jYbhH UfhYs